Insight into vented explosion mechanism and premixed flame dynamics in linked vessels: Influence of membrane thickness and blocking rate. (September 2021) - Sun, Weikang; Liu, Lijuan; Li, Yi; Huang, Chuyuan; Chen, Xianfeng; Feng, Mengmeng
Abstract: To effectively prevent and mitigate explosion hazards and casualties, relief venting of flammable gas explosions has been applied in production processes in a broad variety of industries. This work conducted fully vented experiments to investigate the influence of venting membrane thickness, and partially vented experiments to investigate the influence of baffle blocking rate on the explosion characteristics of 9.5 vol% methane-air mixtures in linked vessels with a 0.5 m long vented duct. Results indicate that the membrane thickness and blocking rate for the two types of vented explosions significantly affected the explosion overpressure. The smaller the membrane thickness and blocking rate, the lower the explosion overpressure. Secondary explosions were observed in the vented duct through experiments and a weaker explosion flame appeared at a small blocking rate of 20%. With the further increase in the blocking rate, the flame became extremely weak, and no secondary explosions occurred. The overpressure evolution process at different positions in the explosion duct and secondary explosion phenomenon in the vented duct were investigated. This work could probably serve as an important reference for the selection of technical parameters of explosion venting in the practical industrial processes. Highlights: The influence mechanism of fully vented and partially vented explosions was revealed. Secondary explosions were only observed in fully vented explosion experiments. Explosion evolution process with membrane rupture and blocking rate was investigated. High-speed jet, rapid descending and steady ascending of flame velocity were divided.